Lung procurement after circulatory death from donor supported on biventricular assist devices and functional assessment with portable normothermic ex vivo organ care system. (5th October 2019) - Ali, Jason M; Kaul, Pradeep; Jenkins, David P; Berman, Marius
Abstract: The criteria for donor organ acceptance are broadening. We describe a successful lung transplantation following donation after circulatory death of extended criteria donor supported with biventricular assist devices. During the redo sternotomy, we used the biventricular assist devices cannulae to perfuse the lungs through the pulmonary artery cannula and draining via the left and right ventricle cannula, significantly minimizing the ischaemic time. Following procurement, we utilized portable ex vivo lung system (Transmedics™ Lung OCS) to optimize, assess and eventually to proceed to a successful transplant.